Relationship between sport participation and attendance at sporting events. A case study on the judo in Spain - Mateu, Pau; Inglés, Eduard (Revista de Artes Marciales Asiáticas, 2016)
This research aims to show the profile of attendees to judo competitions in Spain, as well as the relationship between sports participation and attendance to judo events. The sample consisted of 270 people who attended three absolute and senior judo events of different competitive levels. Data collection was carried out through questionnaires which were administered during the celebration of the studied events. Frequency and percentage analysis, means comparisons between sexes and contrast procedures were performed. The information obtained shows the majority profiles of people attending judo competitions in Spain. It also establishes a positive link between sport participation and judo events attendance, just as it shows a high proportion of judo players and former judo players at events in this sporting discipline. This study is a step forward in the field of attending martial arts events and contact sports in Spain, and opens the possibility to continue studying on the subject, both in the case of judo so as in other disciplines.